Cryptocurrencies and finance theories / Abdul Quddoos Abdul Basith, Mohammed M Elgammal and Bana Abuzayed - Abdul Basith, Abdul Quddoos; Abuzayed, Bana; M Elgammal, Mohammed (Universiti Teknologi MARA, 2021)
Cryptocurrency (CCY) as a new key player in the currency system that has drawn the attention of scholars to examine its influence, relations and the opportunities that it may provide. However, a financial theoretical framework to connect CCY with financial theory is missing. This paper fills this gap by providing a review for the theoretical framework introduced in the literature to position CCY in investment and finance theories. This is done by studying the CCY literature and providing a critical feedback on the overall contributions in the area and possible venues for improvement. We report a need for a long-term analysis for CCY as this asset class is fairly new and sufficient data may not be available. Moreover, a better connection and linking with finance theories is required as it is significantly deficient. The promising potential of block chain/ CCY stresses the need for interdisciplinary research including business, legal and information technology disciplines. In addition, the Covid-19 pandemic opens the door for further research to investigate the role of CCY as a hedge in the times of crises.